Signalling cognition: the gut microbiota and hypothalamic-pituitary-adrenal axis - Rusch, Jody A.; Layden, Brian T.; Dugas, Lara R. (Frontiers in Endocrinology, 2023)
Cognitive function in humans is dependent on a complex and dynamic interplay between multiple body systems, including the hypothalamic-pituitary-adrenal (HPA) axis, and a pivotal role for the gut microbiota is only now being acknowledged. Indeed, the human body contains more microbes in the gut than the total number of human cells, and their genetic potential vastly exceeds that of the human genome. Initially, bidirectional signalling between the brain and the gastrointestinal tract (gut-brain axis) was demonstrated, followed by a growing body of evidence elucidating microbiota-gut-brain axis interactions via endocrine, neural, immune and metabolic pathways. One of the major neuroendocrine systems responding to stress is the HPA axis which produces glucocorticoids such as cortisol in humans and corticosterone in rodents. Cortisol is also a major factor influencing neurodevelopment and function, and appropriate concentrations are essential for normal cognitive processes such as learning and memory. Evidence indicates that throughout life microbes modulate the HPA axis, while stress can significantly impact the microbiota-gut-brain axis via the HPA axis, and other pathways. Animal research has been instrumental in our understanding of these mechanisms and pathways, eliciting a paradigm shift in conceptual thinking about the influence of the microbiota on human health and disease. Preclinical and human trials are currently underway to determine how these animal models translate to humans. The aim of this review article is to summarise the current knowledge of the relationship between the gut microbiota, HPA axis, and cognition.